General Amination Reactions for the Synthesis of Ynamides - Evano, Gwilherm; Jouvin, Kévin; Coste, Alexis (Synthesis, 2013)
The development of general syntheses of ynamides and related compounds based on various amination strategies are described in this short review. Reactions are classified according to the type of amination used and comparisons are made between all strategies to provide a comprehensive overview and to emphasize the advantages and limitations of each method.1 Introduction: The ABC of Ynamides2 Synthesis of Ynamides at the Dawn of the 21st Century: Elimination and Isomerization3 Synthesis of Ynamides by Amination of/with Hypervalent Iodonium Salts4 The Emergence of General Syntheses of Ynamides: Copper-Mediated Amination of Bromoalkynes, gem-Dibromoalkenes, and Alkynyl(triaryl)bismuthonium Tetrafluoroborates5 Alternative Practical and Mild Syntheses of Ynamides: Copper-Catalyzed Oxidative Amination of Alkynes, Potassium Alkynyltrifluoroborates, and Propiolic Acids6 ‘Click’ Oxidative Amination of Copper Acetylides: A Practical Entry to Ynamides under Mild Conditions7 Synthesis of Ynehydrazides by Electrophilic Amination of Lithium Acetylides with Diazodicarboxylates8 Conclusions and Outlook: Ynamides Synthesis, Where Now?
Keywords: ynamines; ynamides; N-alkynyl heterocycles; amination; copper catalysis; alkynes